2018
DOI: 10.3389/fcimb.2018.00417
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Mycobacterium tuberculosis Clinical Isolates Is Associated With Sputum Pre-treatment Bacterial Load, Lineage, Survival in Macrophages, and Cytokine Response

Abstract: It is uncertain whether differences in Mycobacterium tuberculosis (Mtb) virulence defined in vitro influence clinical tuberculosis pathogenesis, transmission, and mortality. We primarily used a macrophage lysis model to characterize the virulence of Mtb isolates collected from 153 Vietnamese adults with pulmonary tuberculosis. The virulence phenotypes were then investigated for their relationship with sputum bacterial load, bacterial lineages, bacterial growth, and cytokine responses in macrophages. Over 6 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…However, prolonged IL-1β expression could lead to serious tissue injury [ 39 , 40 ]. Virulent Mtb strain can induce a significant amount of IL-1β compared with less virulent strains [ 41 ]. Mtb early secretory antigenic target-6KDa (ESAT-6) can induce IL-1β from the peripheral blood macrophages obtained from latent TB patients compared with the cells from active TB patients [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prolonged IL-1β expression could lead to serious tissue injury [ 39 , 40 ]. Virulent Mtb strain can induce a significant amount of IL-1β compared with less virulent strains [ 41 ]. Mtb early secretory antigenic target-6KDa (ESAT-6) can induce IL-1β from the peripheral blood macrophages obtained from latent TB patients compared with the cells from active TB patients [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that Ms_Rv0341 stimulated a more significant expression of TNF-α than Ms_Vec. Elevated levels of TNF-α were linked with hyper-virulent Mtb strains and increased number of bacilli in the patient’s sputum [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…At 24 h and 72 h after infection, both extracellular bacteria released from macrophage lysed in supernatant and intracellular bacteria in intact cell layer were harvested. Bacteria at 4 h, 24 h and 72 h were plated on 7H10 agar plates in triplicate, plates were incubated for 3 weeks at 37°C and CFU (colony forming unit) were counted [13].…”
Section: Survival Of Rv3737 Knockout Strain In Raw 2647mentioning
confidence: 99%
“…After neutralization and centrifugation, the suspension of the pellet was inoculated on Lowenstein-Jensen (L-J) medium. The visible growth of colonies on L-J medium was identified using conventional biochemical method [13].…”
Section: Sputum Collection Bacterial Growth and Bacterial Load Measumentioning
confidence: 99%
“…High virulence strains also replicated faster in the macrophages and induced lower secretion of tumor necrosis factor α (TNF-α) and IL-6, but higher production of IL-1β. This high virulence bacterial phenotype was strongly associated with lineage 2 strains (Tram et al, 2018). However, this study did not address a possible “fit” between host and Mtb genetic background.…”
Section: The Interplay Of Mtb Lineage and The Human Hostmentioning
confidence: 99%